Hubungan Konsepsional Antara Perpustakaan, Penelitian, Dan Karya Ilmiah - Sholeh, Muhtar Arifin (Kopertais Wilayah X Jawa Tengah, 2019)
The main purpose of this article is to draw the conceptional relation among library, research, and scientific work. Library is traditionally considered as a place of book collection, a reading room, or 'a small waste room’, which show ’a narrow vision’. However, as learning source, library is a place of study, which requires good facility such as providing reading room, complete collection, clear light, good air circulation, etc. It should also be supported by friendly and helpful staff.The relation between research and scientific work is that the report of research should be academically written in national or international journal as a scientific work. In the relation to this, library is a reservoir of collection (printed and non printed collection), including scientific works. In other word, scientific work, like journal or book, should be made as a report of research. Library, research, and scientific work are different from each other, but they can not be separated to each other.